Delayed growth rate based on bone age in children with idiopathic nephrotic syndrome at a general hospital in Banda Aceh, Indonesia - Haris, Syafruddin; Dimiati, Herlina; Hasballah, Kartini; Pardede, Sudung O. (School of Medicine, Universitas Syiah Kuala, 2024)
Paediatric nephrotic syndrome is the most common kidney disease in children, with corticosteroids as the primary treatment. While effective, corticosteroid therapy may decrease bone mineral density. Concurrent vitamin D and calcium supplementation can mitigate bone loss but does not entirely prevent it and may introduce side effects. This study assessed growth delay based on bone age in children with idiopathic nephrotic syndrome receiving long-term steroid therapy at Dr. Zainoel Abidin Public Hospital in Banda Aceh, Indonesia. This observational analytic study used a retrospective cohort design, with data collected from the hospitals Paediatric Polyclinic over one month. Paediatric patients diagnosed with INS who met inclusion criteria were included, and data were extracted from electronic medical records. Statistical analysis was conducted using the Mann-Whitney test. Among the 50 children included, 32 (64%) were male and 18 (36%) were female. The median corticosteroid therapy duration was 24 months (range: 284 months). No significant association was found between corticosteroid therapy duration and growth delay, as measured by BA (p=0.363). INS was more common in boys, particularly in the six to 10-year age group. Most participants had normal nutritional status and stature, with steroid-resistant nephrotic syndrome being the most prevalent type. The findings suggest no relationship between corticosteroid therapy duration and growth delay based on bone age, providing reassurance about the treatments impact on growth outcomes.